Lethal toxicity of phosphamidon on the juveniles of Anahas testudineus (Bloch) and Etroplus maculatus (Bloch) - Anna Mercy, T V; Kurup, B Madhusoodana; Nair, J R; Sulekha, B T (Indian Journal of Fisheries, 2011)
The present study was undertaken to delineate the lethal toxicity of phosphamidonwhich is a widely used organophosphate pesticide in the paddy fields in Kuttanadthe rice bowl of Kerala on Anabas testudineus and Etroplus maculatus. these twospecies of fishes have important share to contribute to the fishery wealth ofKuttanad. The 48 h LC^^ values of phosphamidon for Anabas and Etroplus werefound to be 39.34 and 2.97 ppm respectively. From the experimental results itis apparent that Anabas is much more resistant to phosphamidon than Etroplus.Anabas being an obligate air breathing fish takes in only les pesticide through thegill. These LCj^ values can be utilised for sublethal toxicity studies, which willhelp to arrive at a maximum allowable toxicant concentration.